Sears Building at 16 Court Street, June 1967 - Unknown (Tufts Archival Research Center, 2005)
Street-level view southwest of the Sears Building, located at 16 Court Street at the southwest corner of Court and Washington Streets. The facade of the building faces north towards Court Street. An automobile is visible on Washington Street along the Sears Building's east elevation. Street lights, traffic signs and pedestrians are included in the photograph. 3 1/8 x 3 1/8 overall 3 1/2 x 3 1/2 Photographs